Companion animal and equine clinical research: a Nordic perspective - Bodil Ström Holst; Alejandro Engelmann; Gittan Gröndahl; Lotta Gunnarsson; Anita Haug Haaland; Anna Hielm-Björkman; Lars Moe; Marie Rhodin; Henrik Rönnberg; Marie Stråhle; Ylva Toljander; Annemarie Thuri Kristensen; et al. (Acta Veterinaria Scandinavica, 2025)
Abstract Background The societal value of cats, dogs and horses is high, and the companion and sport animal health care sector is growing. Clinical research concerning cats, dogs and horses is crucial for the development of evidence-based medical care that benefits animals and their owners, and has implications for human and environmental health from a One Health perspective. Basic information on companion animal and equine research enables more directed measures to improve conditions for research within the area. The aim of the present study was to describe Nordic companion animal and equine clinical research from 2010 to 2019, including bibliometrics, human resources and funding. Results There were 2 042 published research publications originating from Nordic countries on cats (n = 282), dogs (n = 1 086), and horses (n = 781) from 2010 to 2019. The majority (83%) of the publications came from the four Nordic universities with veterinary programs. Seven percent of the publications were collaborations between two or more Nordic universities. Approximately 18% of the PhD theses (178 out of 970) from veterinary faculties or corresponding units concerned these species, most of them dogs (n = 86), followed by horses (n = 64), cats (n = 15) or a combination of these species (n = 13). The scientific areas cardiology, infectious diseases, reproduction, and surgery were prominent for all three species. A large proportion of grants were received from small- to medium-sized funding bodies, mainly funding running costs and only to a limited degree salaries. During 2010–2019, costs for veterinary and other services for cats and dogs steadily increased. The growth of the veterinary healthcare sector was not reflected in an increasing number of clinical research publications, for which no increase was seen after 2014. Conclusions Despite a high societal value of the species, veterinary clinical research on sports and companion animals has not increased, in contrast to the veterinary healthcare sector. Activities stimulating the research area, e.g. funding bodies enabling coverage of salaries, are needed. The development of Nordic veterinary clinical care may benefit from strengthened research cooperation between countries.